2019
DOI: 10.1111/jar.12673
|View full text |Cite
|
Sign up to set email alerts
|

Applying the self‐determination theory to develop a school‐to‐work peer mentoring programme to promote social inclusion

Abstract: Social inclusion of individuals with intellectual and developmental disabilities (IDD) is related to positive mental health and social outcomes; yet, individuals with IDD experience societal barriers that limit opportunities for community participation. Providing opportunities for interactions between individuals with and without IDD through peer mentoring may diminish barriers and improve community inclusion. Guided by the self‐determination theory, the current report describes the development of a peer mento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 60 publications
(93 reference statements)
0
8
0
Order By: Relevance
“…First started in 2016, the Spartan Project SEARCH–Peer Mentoring (SPS-PM; Fisher et al, 2020) program was developed by the second and third authors to promote community inclusion on campus as an additional component of the Project SEARCH program. The SPS-PM program was designed as a peer support social program to encourage inclusion and to create a sense of belonging and connection to the campus community for students with IDD.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…First started in 2016, the Spartan Project SEARCH–Peer Mentoring (SPS-PM; Fisher et al, 2020) program was developed by the second and third authors to promote community inclusion on campus as an additional component of the Project SEARCH program. The SPS-PM program was designed as a peer support social program to encourage inclusion and to create a sense of belonging and connection to the campus community for students with IDD.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the Self-Determination Theory (SDT; Ryan & Deci, 2000; see Fisher et al, 2020) was referenced as a guiding framework in the development of the SPS-PM program which included seven key components: (a) development of a core team of support, (b) recruitment of peer mentors and mentees, (c) disability awareness and etiquette training, (d) peer mentor–mentee matching, (e) weekly meet-ups, (f) monthly social events, and (g) ongoing supports. The program was designed as a social support program where the mentors and mentees were not provided an explicit curriculum to implement; instead, they were encouraged to engage in typical social interactions similar to what they would engage in with their peers without disabilities.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the remaining 28 articles, we excluded 17 articles for the following reasons: was a postsecondary transition/orientation program, [48][49][50] program used but not designed for autistic students, 21,51 lacked some form of program evaluation, [52][53][54][55][56][57] and school-to-work/job coaching program. 58,59 Upon full-text review, we excluded two dissertations. 6,60 Of the 11 studies included in the qualitative syntheses, we identified a total of nine unique programs (Table 1).…”
Section: Systematic Reviewmentioning
confidence: 99%